A Content Analysis of COVID-19 Pro-Vaccine and Ant-Vaccine Internet Memes in Poland - Buczek, Katarzyna (2022)
Faced with Covid-19, people are overwhelmed with information coming not only from governmental, or health care sources, but also from social media and digital communication platforms. The Internet and, especially, social media are often inundated with unreliable or even false information regarding Covid-19 and vaccination against it. This seriously impacts public health, since misinformed people may be hesitant towards the health-related measures enforced by governments and health authorities, which, in turn, contributes to their vaccine hesitancy. The aim of the paper is to investigate the Internet memes created and popularized in Poland by supporters and opponents of Covid-19 vaccinations. The data for the study include memes published between December 2020 (vaccinations become available in Poland) to May 2021 and comes from the most popular, publicly accessible social networks and meme pages with the greatest number of followers. The content analysis rests on such variables as (1) whether the meme is pro- or anti-vaccine, (2) what persuasive appeals (emotion, fear, rationality) are used, (3) the number of reactions and shares. Additionally, the author looks at the thematic content of the memes and tries to specify whether the pro- and anti-vaccination memes contain more gist than verbatim information. The analysis aims to define persuasion methods that pro-vaccine and anti-vaccine groups use in their memes.
Keywords: content analysis; memes; COVID-19; persuasion methods